Studi Analisis Gedung 7 Lantai Menggunakan Program ETABS - Sari Utama Dewi; Samudra Arrazakia (Universitas Darul Ulum, 2026)
The construction of multi-story buildings requires structural designs that ensure safety, strength, and adequate structural performance under various loading conditions. This study aimed to analyze and design reinforced concrete beam elements in a seven-story building using structural analysis software. The object of the study was the Civil Engineering Department building of the Faculty of Engineering at the University of Lampung. Structural analysis was carried out through three-dimensional modeling to evaluate the structural response under load combinations consisting of dead loads, live loads, wind loads, and earthquake loads. The analysis produced internal force responses, including bending moments, shear forces, and torsional forces acting on the beam elements. These results were used to determine appropriate beam dimensions and reinforcement requirements in order to satisfy structural strength and stability criteria. The findings indicated that the designed beam dimensions and reinforcement configurations were capable of resisting the applied load combinations with structural deformations remaining within acceptable limits. Furthermore, the evaluation of structural capacity confirmed that the beam design satisfied the required safety and performance criteria. Therefore, the reinforced concrete beam design for the seven-story building was considered structurally safe and suitable for implementation in multi-story building structural planning.